Warming up to Credit Freeze Laws: The Case of Utah (Hinckley Journal of Politics, 2017)
The high-profile personal information data breaches of 2005 drew considerable public attention to the growing crime of identity theft. In order to equip consumers with tools for ID theft prevention, several states enacted credit freeze laws. Originating in California in 2001, these types of laws allow consumers to have more control over who can access their credit reports by placing a â€œfreezeâ€ on their records. There has been substantial debate regarding the merits of credit freezes. The credit reporting industry sees this process as unnecessary and â€œoverkill,â€ touting their own fraud alerts services as sufficient to protect consumers. Consumer advocates, however, view these laws as one of the strongest protections consumers can have against abuse of their personal credit information. This study advances understanding of credit freeze laws by exploring the main arguments for and against them and detailing the history of Utahâ€™s unique credit freeze law. This study identifies the key factors that aided the lawâ€™s passage in 2006 despite having failed in 2005. This is accomplished through interviews of individuals directly involved with the passage of the law in 2006 and relevant literature in periodicals and government reports. The discussion of Utahâ€™s law emphasizes the differences between it and credit freeze laws passed in other states as well as proposed national legislation. Finally, this study speculates on the future of credit freeze laws in Utah and nationally. The passage of Utahâ€™s law with its unique 15-minute freeze feature has created an intriguing situation for other states and the credit industry. It has in essence drawn a line in the sand â€” for other states, the credit bureaus, and the federal government â€” to cross over or retreat from in determining national policy regarding the future of credit freeze laws